PELATIHAN DAN PENDAMPINGAN PEMBELAJARAN BERBASIS HYBRID DENGAN MENGGUNAKAN E-LEARNING UNTUK GURU FISIKA SMA DI SITUBONDO SELAMA MASA PANDEMI - Supriyono Koes H; Sahal Fawaiz; Ahmad Suryadi; Amaliyah Tazkiyah; Alif Darmawan; Khusnul Nurhidayah (Bahasa Indonesia, 2021)
The Covid-19 pandemic caused many schools to close and forced educators to replace face-to-face learning to online learning overnight. The process of transitioning to the application of distance learning cannot occur in a short time. So that it takes adequate facilities and teacher skills in designing learning. E-learning facilities are still unfamiliar to both teachers and students, especially in Situbondo Regency. So that mentoring and training in the use of e-learning for teachers in physics learning is needed to make it easier for teachers and students in the learning process. Planning activities include making e-learning modules using moddle and camtasia. The training and mentoring process was even attended by 93 physics teachers outside Situbondo Regency. However, those who can participate in the training gradually decrease due to the busyness of each participant. So that at the end of the Moodle e-learning training and mentoring session, there are 25 (18 from Situbondo) participants who can design a complete lesson including assignment features, quizzes (aiken format), labels, lessons, Bigblue buttons, pages, books and forums. Keywords: Abstrak Masa pademi covid-19 menyebabkan banyak sekolah tutup dan memaksa pendidik mengganti pembelajaran tatap muka ke pembelajaran online dalam waktu singkat. Proses transisi penerapan pembelajaran jarak jauh tidak bisa terjadi dalam waktu yang singkat, sehingga dibutuhkan fasilitas dan keterampilan guru yang memadai dalam merancang pembelajaran. Fasilitas e-learning pun masih asing baik bagi guru maupun siswa, khususnya di Kabupaten Situbondo. sehingga pendampingan dan pelatihan penggunaan e-learning untuk guru dalam pembelajaran fisika dirasa sangat dibutuhkan untuk mempermudah guru dan siswa dalam proses pembelajaran. Perencanaan kegiatan meliputi pembuatan modul e-learning menggunakan moddle dan camtasia. Proses pelatihan dan pendampingan diikuti bahkan oleh guru fisika di luar Kabupaten Situbondo sebanyak 93 peserta. Namun yang dapat mengikuti pelatihan secara bertahap berkurang karena kesibukan masing-masing peserta. Sehingga di akhir sesi pelatihan dan pendampingan e-learning moodle terdapat 25 (18 dari Situbondo) peserta yang dapat merancang pembelajaran secara lengkap meliputi fitur assignment, quiz (aiken format), label, lesson, Bigblue button, page, book dan forum.